Structure‐aware dehazing of sewer inspection images based on monocular depth cues. (1st August 2022) - Xia, Zixia; Guo, Shuai; Sun, Di; Lv, Yaozhi; Li, Honglie; Pan, Gang
Abstract: In sewer pipes, haze caused by the humid environment seriously impairs the quality of closed‐circuit television (CCTV) images, which leads to poor performance of subsequent pipe defects detection. Meanwhile, the complexity of sewer images, such as steep depth change and extensive textureless regions, brings great challenges to the performance or application of general dehazing algorithms. Therefore, this study estimates sewer depth maps first with the help of the water–pipewall borderlines to produce the paired dehazing dataset. Then a structure‐aware nonlocal network (SANL‐Net) is proposed with the detected borderlines and the dehazing result as two supervisory signals. SANL‐Net shows its superiority over other state‐of‐the‐art approaches with 147 in mean square error (MSE), 27.28 in peak signal to noise ratio (PSNR), 0.8963 in structural similarity index measure (SSIM), and 15.47M in parameters. Also, the outstanding performance in real image dehazing implies the accuracy of depth estimation. Experimental results indicate that SANL‐Net significantly improves the performance of defects detection tasks, such as an increase of 23.16% in mean intersection over union (mIoU) for semantic segmentation.